2016
DOI: 10.1136/thoraxjnl-2015-208035
|View full text |Cite
|
Sign up to set email alerts
|

Metformin in severe exacerbations of chronic obstructive pulmonary disease: a randomised controlled trial

Abstract: BackgroundSevere exacerbations of COPD are commonly associated with hyperglycaemia, which predicts adverse outcomes. Metformin is a well-established anti-hyperglycaemic agent in diabetes mellitus, possibly augmented with anti-inflammatory effects, but its effects in COPD are unknown. We investigated accelerated metformin therapy in severe COPD exacerbations, primarily to confirm or refute an anti-hyperglycaemic effect, and secondarily to explore its effects on inflammation and clinical outcome.MethodsThis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 34 publications
2
54
0
1
Order By: Relevance
“…More recently, Tseng reported that the use of metformin was associated with approximately 40% lower risk of COPD . Yet, not all results are consistent: a recent multicentre, randomized, double‐blind, placebo‐controlled trial found no effect of metformin administration on glucose elevations during COPD exacerbations, inflammation or COPD assessment test . The trial was however small, including 52 participants randomized to receive either metformin (34 participants) or placebo (18 participants).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Tseng reported that the use of metformin was associated with approximately 40% lower risk of COPD . Yet, not all results are consistent: a recent multicentre, randomized, double‐blind, placebo‐controlled trial found no effect of metformin administration on glucose elevations during COPD exacerbations, inflammation or COPD assessment test . The trial was however small, including 52 participants randomized to receive either metformin (34 participants) or placebo (18 participants).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have examined the association of metformin use with the development of asthma and/or COPD as well as the morbidity related to these conditions in diabetic patients . However, it is not known whether metformin use reduces CLRD mortality among in patients with T2D.…”
Section: Introductionmentioning
confidence: 99%
“…In non-diabetic patients metformin did not ameliorate acute exacerbations [33], but exerted positive effects on symptoms, health status, inspiratory muscle function, lung hyperinflation and gas trapping in a prospective open-label study of moderate to severe COPD patients with diabetes and BMI > 25 kg/m 2 [34]. Possibly the beneficial effects of anti-diabetic drugs on the lung occur only in the presence of definite inflammatory lung disease such as COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Of 1332 patients with both diseases, one‐third were on metformin and those patients had a lower risk of asthma exacerbation and asthma‐related hospitalization, suggesting that this might be an effective treatment for this patient population . This result contrasted with data evaluating metformin in a randomized controlled trial to treat patients with chronic obstructive pulmonary disease (COPD), which found that metformin had no effect on the severity of COPD exacerbations, indicating that the positive effects may not extend to other lung diseases.…”
Section: Myeloid‐modulating Agentsmentioning
confidence: 93%